The outperformance of the semantic learning machine, against commonly used algorithms, for binary and multi-class medical image classification: combined with the usage of feature extraction by several convolutional neural networks - Croon, Dennis Gerardus (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics